Single-cell Raman spectroscopy identifies Escherichia coli persisters and reveals their enhanced metabolic activities - Wang, Chuan; Chen, Rongze; Xu, Jian; Jin, Lijian (Frontiers in Microbiology, 2022)
Microbial persisters are the featured tiny sub-population of microorganisms highly tolerant to multiple antimicrobials. Currently, studies on persisters remain a considerable challenge owing to technical limitations. Here, we explored the application of single-cell Raman spectroscopy (SCRS) on the investigation of persisters. E. coli (ATCC 25922) cells were treated (4 h) with lethal dosage of ampicillin (100 μg/mL, 32×MIC) for the formation of persisters. The biochemical characters of E. coli and its persisters were assessed by SCRS, and their metabolic activities were labelled and measured with D2O-based single-cell Raman spectroscopy (D2O-Raman). Notable differences in the intensity of Raman bands related to major cellular components and metabolites were observed between E. coli and its ampicillin-treated persisters. Based on their distinct Raman spectra, E. coli and its persister cells were classified into different projective zones through the Principal Component Analysis and t-Distributed Stochastic Neighbor Embedding. According to the D2O absorption rate, E. coli persisters exhibited higher metabolic activities than those of untreated E. coli. Importantly, persister cells began to absorb D2O for metabolism shortly after the termination of ampicillin treatment. To our knowledge, this is the first report on identifying E. coli persisters and assessing their metabolic activities by the integrated SCRS and D2O-Raman approach. These novel findings enhance our understanding on the phenotypes and functionalities of microbial persister cells. Further investigations could be extended to other pathogens on disclosing microbial pathogenicity mechanisms for developing novel therapeutic strategies and approaches.